Josephus and Jewish History in Flavian Rome and Beyond - Lembi, Gaia; Sievers, Joseph (Supplements to the Journal for the Study of Judaism, 2005)
The essays in this volume focus on the relationship between Josephus' Judean and Jewish identity on the one hand, and his life and writings in the context of Flavian Rome on the other. From very different points of view the various contributions to this volume, which is the fruit of an international colloquium entitled 'Josephus between Jerusalem and Rome' held in the city of Rome in 2003, shed light on the complex cultural interplay in Josephus' writings. After examining more general historiographical and literary questions, the volume proceeds to address specific issues of Josephus' presentation of Judaism and of historical "data", inter alia about the war of 66-70 CE. A final section deals with the translation and transmission of his works.